ANTIINFLAMMATION ACTIVITY ETHANOL EXTRACT OF MARBOSI-BOSI LEAVES (Tarenna polycarpa (Miq.) Koord.Ex Valeton) ON WHITE RAT IN CARRAGEENAN INDUCED PAW INFLAMMATION - munandarnst, haris; N, Marline (Asian Journal of Pharmaceutical Research and Development, 2018)
Traditionally, (Tarenna polycarpa (Miq.) Koord Ex Valeton as known as marbosi-bosi which commonly found in Sibolga, North Sumatera, Indonesia has been used as antidiabetes, cholesterol, anti-inflammatory and antibacterial. Tarenna species has been found its activities as antimicrobial, anti-oxidant and anti-inflammatory activity. The aim of this study was to investigate the anti inflammatory effect ethanol extract of marbosi-bosi leaves (Tarenna polycarpa (Miq.) Koord Ex Valeton in terms of decreased edema volume of male white rat in 1% carrageenan-induced and also to determine the effective dose of extract to decrease the volume of rat paw edema Ethanol extract of marbosi-bosi (Tarenna polycarpa (Miq.) Koord Ex Valeton was obtained by maceration. The antiinflammatory activity test was divided into 5 groups. The Group I (negative control) was given CMC 0.5%, Group II (positive control) was given diclofenac sodium 2,25 mg / kg BW, while Group III, IV and V were given marbosi-bosi leaf extract at a dose of 50, 100 and 200 mg/kgBW respectively. Each rat was induced by 1% carrageenan subplantar injection. Examination of antiinflammatory effect was measured by using digital plethysmometer at minute of 30 to minute of 360. The data were analyzed statistically using ANOVA (analysis of variance).The results showed that negative control did not show anti-inflammatory effect had significant differences with other treatment groups. In conclusion, ethanol extract marbosi-bosi (Tarenna polycarpa (Miq.) Koord Ex Valeton has an effective anti-inflammatory activity at a dose of 100 mg / kgBW.